Relationship between retinal vessel diameter with both retinal nerve fibre layer thickness and optic nerve head parameters in middle‐aged Caucasians: the Northern Finland Birth Cohort Eye study - Geneid, Mohamed (Acta Ophthalmol, 2018)
PURPOSE: To study the normal relationship between retinal vessel diameter (RVD) with retinal nerve fibre layer (RNFL) thickness and optic nerve head (ONH) parameters in a cohort of middle‐aged Caucasians. METHODS: We investigated 3070 individuals (6140 eyes). Central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) were measured in the right eye using a semi‐automated computer‐assisted program. Retinal nerve fibre layer (RNFL) thickness and ONH parameters were assessed with Heidelberg retinal tomography (HRT). RESULTS: Data from 2217 persons were analysed including RNFL, CRAE, CRVE, sex, body mass index, mean arterial pressure, diabetes status, smoking status, optic disc area, rim area, spherical refraction and intraocular pressure. A larger RVD was associated with a thicker mean global RNFL thickness especially in global and inferior segments of the retina and with larger optic discs. Each 10 μm increase in the retinal arteriolar calibre was associated with a 5.58 μm increase in mean global RNFL thickness; the corresponding value for a 10 μm increase in venular calibre was 3.79 μm (p < 0.001 for both). Retinal venular calibre displayed consistent associations with RNFL thickness in both genders (p < 0.001 for all), whereas the association of arteriolar calibre and RNFL was more prominent in men (p < 0.001). CONCLUSION: We found strong associations between larger RVD and thicker RNFL in all subjects. This study helps to clarify the association between RVD, RNFL thickness and ONH parameters and provides normal values for middle‐aged Caucasians that will help in future studies investigating the role of vascular aetiology in systemic and eye diseases.